Integrating Ahlussunnah wal Jama’ah values into Islamic religious education learning management: A case study at MI NU An-Nur Purworejo - Adib Qosim Masrukhan; Abdurrahman Abdurrahman (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose – This study is motivated by the importance of strengthening the management of Islamic Religious Education (IRE) learning based on the values of Ahlussunnah wal Jama’ah in shaping students’ religious and moderate character in madrasahs. Previous studies have generally focused on curriculum implementation and religious habituation, while limited attention has been given to the systematic integration of Aswaja values within the overall management of IRE learning. Therefore, this study aims to analyze the integration of Aswaja values in the planning, implementation, and evaluation of IRE learning at MI NU An-Nur Purworejo. Method – This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, IRE teachers, pesantren ustāẓ, and students. Data validity was ensured through source and technique triangulation. Data analysis was conducted through data reduction, data display, and conclusion drawing to obtain a comprehensive interpretation of the findings. Findings – The findings reveal that Aswaja values are integrated systematically into curriculum planning, learning objectives, instructional activities, religious habituation, and evaluation practices. The internalization of values is strengthened through teacher role modeling, pesantren traditions, hidden curriculum practices, and students’ direct religious experiences within the madrasah environment. In addition, the integration of religious and national values contributes to the development of students’ moderate Islamic character, discipline, tolerance, and social responsibility. The study concludes that the management of Islamic Religious Education learning based on Aswaja values is implemented holistically and consistently through the synergy between instructional management, institutional culture, and character-based educational practices.